Community health worker perspectives: examining current responsibilities and strategies for success - Monica Kowalczyk; Nicole Yao; LaToya Gregory; Jeannine Cheatham; Tarrah DeClemente; Kenneth Fox; Stacy Ignoffo; Anna Volerman (BMC, 2024)
Abstract Background Community health worker (CHW) interventions have demonstrated positive impacts globally, with the COVID-19 pandemic further highlighting the potential of CHWs at the frontline to support prevention, outreach, and healthcare delivery. As the workforce expands, understanding the work and capabilities of CHWs is key to design successful interventions. This study examines the perspectives of experienced CHWs in Chicago about their current work and strategies for success. Methods As part of a community-academic partnership in Chicago, semi-structured interviews were completed with individuals who held positions aligned with CHW. Interviews were conducted between January and April 2022. Questions focused on participants' work and factors contributing to their effectiveness to gain insights into workforce strategies for success to be applied in healthcare and community settings. De-identified transcripts were analyzed using inductive reasoning with codes organized into themes and subthemes under two domains identified a priori. The themes informed a logic model focused on the early stages to support the success of CHWs in their role. Results Fourteen individuals participated in the study. The two predetermined domains in this study were: current work of CHWs and strategies for CHWs to be successful. Five themes were identified about CHWs' current work: providing services, building alliances with clients, establishing and maintaining collaborations, collecting data, and experiencing challenges in role. From their perspectives, all these responsibilities enhance client care and support workforce sustainability efforts. Five themes emerged about strategies for the success of CHWs: background of CHWs, champions to support work of CHWs, materials to perform work of CHWs, preparation for CHW role, and characteristics of CHWs. Participants described key traits CHWs should possess to be hired, individuals who can champion and advocate for their work, and specific materials needed to fulfill responsibilities. They reported that training and familiarity with the community were integral to developing and refining the qualities and skills necessary to be effective in their role. Conclusion CHWs play an increasingly important role in enhancing healthcare delivery and improving health outcomes. This study offers a framework for policymakers, communities, and organizations to utilize for preparing CHWs to succeed in their roles.